2022
DOI: 10.1186/s12711-022-00730-w
|View full text |Cite
|
Sign up to set email alerts
|

A new approach fits multivariate genomic prediction models efficiently

Abstract: Background Fast, memory-efficient, and reliable algorithms for estimating genomic estimated breeding values (GEBV) for multiple traits and environments are needed to make timely decisions in breeding. Multivariate genomic prediction exploits genetic correlations between traits and environments to increase accuracy of GEBV compared to univariate methods. These genetic correlations are estimated simultaneously with GEBV, because they are specific to year, environment, and management. However, est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, the results of model M3 (also including the interaction between family and environment) were similar to those obtained by Persa et al, 2020 analyzing information of the SoyNAM experiment comprising 1,358 RILs observed in 18 environments (not all RILs observed in all environments) but considering a conventional fivefold cross-validation predicting tested genotypes in observed environments (CV2) and untested genotypes in observed environments (CV1). In addition, Xavier and Habier (2022), using the SoyNAM population conducted an study to evaluate the effects in predictive ability of models similar to M1 and M2 when considering simulated data for the case where RILs are observed only once across environments for different heritabilities. The results obtained for these authors were higher compared with the results here presented probably due to the fact they considered simulated data as response as opposed to real data and a different cross-validation scheme.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of model M3 (also including the interaction between family and environment) were similar to those obtained by Persa et al, 2020 analyzing information of the SoyNAM experiment comprising 1,358 RILs observed in 18 environments (not all RILs observed in all environments) but considering a conventional fivefold cross-validation predicting tested genotypes in observed environments (CV2) and untested genotypes in observed environments (CV1). In addition, Xavier and Habier (2022), using the SoyNAM population conducted an study to evaluate the effects in predictive ability of models similar to M1 and M2 when considering simulated data for the case where RILs are observed only once across environments for different heritabilities. The results obtained for these authors were higher compared with the results here presented probably due to the fact they considered simulated data as response as opposed to real data and a different cross-validation scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Although promising, the applicability of genomic prediction for seed oil content is still negligible for many soybean breeding programs given the relatively low cost and high‐throughput assessment of seed composition through near‐infrared reflectance spectroscopy (NIRS) compared to genotyping costs. Nevertheless, multivariate genomic prediction models leveraging the genetic correlations among traits of interest (Xavier & Habier, 2022) can be explored to improve the identification and selection of genotypes with desirable oil content and/or fatty acid profile and grain yield simultaneously.…”
Section: Oil and Fatty Acidsmentioning
confidence: 99%